2002
DOI: 10.1007/s00403-002-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the vitamin D3 receptor in patients with psoriasis

Abstract: 1,25-Dihydroxyvitamin D is the biologically active form of vitamin D for the treatment of skin eruptions in patients with psoriasis. 1,25-(OH)(2)D(3) elicits its action on skin eruptions through the vitamin D receptor (VDR). Allelic frequencies of VDR were studied in 86 normal subjects and 50 patients with psoriasis. Genomic DNA was extracted from peripheral blood leukocytes and the VDR gene was amplified using a heminested polymerase chain reaction (PCR). The products were digested with respective restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 11 publications
7
62
0
Order By: Relevance
“…Calcitriol is involved in the regulation of antimicrobial peptides cathelicidin and human -defensin 2 (HBD2), which both participate in the pathogenesis of psoriasis (22). Vitamin D's role in psoriasis is further supported by studies that confirm the link between VDR polymorphism and psoriasis (23,24). An association between VDR genotypes (Apa1) and the mean age at onset of psoriasis were previously observed (25).…”
Section: The Effects Of Vitamin D In Psoriasismentioning
confidence: 90%
“…Calcitriol is involved in the regulation of antimicrobial peptides cathelicidin and human -defensin 2 (HBD2), which both participate in the pathogenesis of psoriasis (22). Vitamin D's role in psoriasis is further supported by studies that confirm the link between VDR polymorphism and psoriasis (23,24). An association between VDR genotypes (Apa1) and the mean age at onset of psoriasis were previously observed (25).…”
Section: The Effects Of Vitamin D In Psoriasismentioning
confidence: 90%
“…The gene encodes a polypeptide that binds 1,25-dihydroxy-calciferol (activated vitamin D) and interacts with target nuclei to produce a variety of effects. VDR has been shown to be present in significant concentrations in T lymphocytes and macrophages (19), and some of its polymorphisms have recently been found to be associated with several autoimmune diseases in man, such as psoriasis (20), Grave's disease (21,22), Addison's disease (23) and T1D (24 -31). In addition, the VDRF and VDRB single nucleotide polymorphisms (SNPs) were suggested to have an effect on GAD65-autoantibody positivity in T1D (30) and on the onset pattern of the disease (31), respectively, in Japanese case-control analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies [5][6][7][8][9][10] reported an association between psoriasis and VDR polymorphisms. In a Korean population, a significant difference in VDR genotypes between normal controls and psoriatic patients, especially those with early onset, was demonstrated [5].…”
mentioning
confidence: 99%